HEGEMONI PEREMPUAN TERHADAP PEREMPUAN DALAM SATUA MEN TIWAS TEKEN MEN SUGIH - Ida Bagus Gede Paramita; Ni Ketut Sri Indra Artiningsih; Ni Kadek Nia Ciptariani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Men against women usually do hegemony. However, it does not rule out the possibility that women can do hegemony over their fellow human beings. Even if women do hegemony towards women, their form can be more sadistic than male hegemony towards women. They are not only found in real life but also in texts of literary works such as in Satua Men Tiwas signed Men Sugih, where this literary work is one of the well-known ones in Bali. In each of the Men Tiwas signed by Sugih, Men described the hegemony of Men Sugih towards Men Tiwas, where the economic levels of both of them are inversely proportional. Like the concept of karmapala in Bali, in this literature Men Sugih also got karmapala due to his sadistic actions towards Men Tiwas.